High-quality carrots in relation to the superior phloem parenchyma cells and proportion of xylem vessel in coordinated water-fertilizer management - Zhao, Ying; Gong, Yanchen; Li, Yun; Xin, Hua; Chi, Ruiping; Chen, Yanling (Frontiers in Plant Science, 2025)
BackgroundThe coordinated management of water and fertilizer is essential for improving vegetable yield and quality. However, its role in connecting quality with the anatomical structure of the phloem and xylem in carrots remains unclear.MethodsThis study involved a two-year field trial with four different water and fertilizer treatments: farmer practices (FP), an optimized water and fertilizer system (OPT), 30% organic substitution with compressed peanut shells (PS), and 30% organic substitution with Pleurotus ostreatus residue (M) combined with water and fertilizer optimization.ResultsCompared with the FP treatment, the OPT, PS, and M treatments increased both yield and quality. Flavor quality increased by 17.51%, 13.04%, and 15.05%, and nutritional quality increased by 11.04%, 8.12%, and 17.35% in the upper, middle, and lower segments, respectively, in the OPT treatment. In contrast, the organic substitution treatments (average of PS and M) resulted in even greater improvements, with flavor quality increasing by 32.50%, 18.21%, and 38.07%, and nutritional quality increasing by 10.28%, 4.69%, and 25.41%, respectively. In the phloem, flavor and nutritional quality increased by 9.59% and 13.50%, respectively, in the OPT treatment and by 12.35% and 17.69%, respectively, in the organic substitution treatment. In the xylem, flavor and nutritional quality increased by 1.64% and 19.09%, respectively, in the OPT treatment, whereas in the organic substitution treatments, flavor quality increased by 16.89%, and nutritional quality increased by 1.94%. Compared with those in the FP treatment, the phloem parenchyma cell area (Pca) and the proportion of xylem vessels to secondary xylem (Pxv) in the upper segment were 9.17% and 88.40% greater in the OPT treatment, respectively, and 18.44% and 116.22% greater in the organic substitution treatment, respectively. The parameters characterizing Pca and Pxv in the upper segment, along with Pca in the lower segment, were positively correlated with flavor and nutritional quality, whereas the xylem vessel area (Xva) and diameter (Xvd) were negatively correlated.ConclusionIn conclusion, the coordinated management of water, organic, and inorganic fertilizers improves flavor and nutritional quality across the upper, middle, and lower segments, as well as in the phloem and xylem. The superior phloem parenchyma cell area and xylem vessel proportion in the upper segment may serve as physiological traits in breeding carrots for quality improvement.